The promises and limitations of devolution and local forest management in China - Liu Dachang; Edmunds, D. (Routledge, 2003)
This chapter examines China’s experiment on devolution policies for local forest management. These policies included the transfer of forest management from collectives to households, the involvement of villagers in the management of state forests, and the shift of some decision-making authority in forest management from community and forestry department to more local entities, such a village comities (VCs). The chapter explores the impact of those policies, explains why they have not always lived up to the expectations, of either farmers or government officials. It was found that devolution experience in China have expanded local decision-making authority in forest management, increase the material and environmental benefits that farmers receive from forest and improved forest cover. Another impact is that the local social capital and institutional capacity are stronger as the state has helped to improve local technical expertise and marketing conditions.